The Relationship between Psychological Wellbeing and Self- Care among Elderly Residents in Iraq - Bashaer Mohsen Ali; Ali Kareem Al-Juboori (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aging is described as progressive change in psychological, biological and social structure of persons. Theadvanced age contributed negatively to self-care. The relocation to care homes considered as stressful eventfor the elderly people. The purpose of this study to find the relationship between psychological well-beingand self-care among the elderly residents at nursing homes in middle Euphrates in Iraq. A descriptivecorrelationaldesign was used to gather the information from the sample of 60 participants in nursing homes.The study has been carried out from November, 1st, 2019 to August, 2020. Purposive sample used to collectthe data according to some criteria. The data collected by means of Ryff scales of psychological well-being(shorten version) and self-care questionnaire as well as the socio-demographical of study sample. The datacollected by using structured interview technique with the elderly residents in nursing homes. The datacollected by means of Ryff scales of psychological well-being (shorten version) and self-care questionnaire aswell as the socio-demographical of study sample. The data collected by using structured interview techniquewith the elderly residents in nursing homes. The results of study indicate that a relationship exists betweenpsychological well-being and self-care among the elderly residents in nursing homes. As the relationshipbetween the two variables is a high significant positive relationship (r = 0.721). The recommendations focuson managing the problems existing among the elderly and monitoring their psychological state. Establishingeducational programs on how to focus on the psychological and physical aspects. In addition, increasingleisure trips to various places.